دور اللغة في تحقيق فعالية الاتصال الإداري - زوزو, الأستاذ الدكتور: رشيد; بوحنيك, الباحثة، زينب (Sciences de l'Homme et de la Société, 2015)
تعتبر الفعالية ضرورة ملحة لكل العمليات الإدارية، خاصةً إذا أردنا تحقيق الأهداف المختلفة للتنظيم، القريبة والبعيدة، لكن هناك بعض العمليات التي تحتاج إلى فعالية أكثر داخل التنظيم، لأن التنظيم يعتمد عليها اعتمادًا كبيرًا، منها عملية الاتصال الإداري، التي تعتبر عملية محورية تقوم على تبادل المعلومات والبيانات، والتوجيه، لإجراء بقية العمليات الإدارية. ونظرًا لأهمية الاتصالات الإدارية فإن دراستها باتت لا تقل أهمية، عن دراسة التنظيم ككل، خاصةً ما تعلق بوسائلها كاللغة المستخدمة وطرق توظيفها، ومن ثَمَّ جاءت هذه الدراسة هادفة إلى معرفة دور اللغة في تحقيق فعالية الاتصال الإداري.   Abstract: Event is an urgent necessity for all administrative processes, especially if we are to achieve the objectives of the regulation, but there are some operation that you need to more effectively within the organization, because the organization depends heavily, the administrative contact, which is a central process based on the exchange of information and data, and guidance for the rest of the administrative processes. Given the importance of administrative communication, the study is not less important than the study of the organization as a whole, particularly as concerned the means as the language used and the methods employed, and then came the study to determine the role of language in communication administrative effectiveness.